Cancer care for people with mental disorders: A qualitative survey among cancer care and psychiatric care professionals in Japan. Issue 12 (26th August 2021) - Etoh, Tsuyoshi; Fujiwara, Masaki; Yamada, Yuto; Wada, Riho; Higuchi, Yuji; Inoue, Shinichiro; Kodama, Masafumi; Matsushita, Takanori; Yoshimura, Yusaku; Horii, Shigeo; Fujimori, Maiko; Kakeda, Kyoko; et al.
Abstract: Objective: It is widely assumed that there are multiple levels (from individual to policy level) of problems involving disparities in cancer care for people with mental disorders. However, few studies have comprehensively investigated issues as perceived by medical professionals. The purpose of the present study was to identify a wide range of issues in cancer care for people with mental disorders and offer corresponding solutions for both cancer care professionals and psychiatric care professionals. Methods: We distributed open‐ended questionnaires to 754 healthcare professionals in various medical facilities, including designated cancer hospitals, psychiatric hospitals, and other local healthcare/welfare facilities. Participants were asked to describe issues in cancer care for people with mental disorders. Results: Of the 754 recruited professionals, 439 (58.2%) responded to the questionnaire. Sixty‐one issues were extracted and categorized into 10 categories: patient factors; isolation and lack of support; obstacles to transport; socioeconomic factors; attitudes of psychiatric professionals; medical system of psychiatric hospitals; attitudes of cancer care professionals; medical system of designated cancer hospitals; regional cancer medical systems; and lack of coordination among multidisciplinary healthcare professionals. Forty‐eight specific solutions were summarized into 12 goals. Conclusions: The present study widely identified issues causing disparities in cancer care for patients with mental disorders. We found that the issues extended from the patient level to the public‐policy level. Our findings suggest the need for a multidisciplinary approach that includes both cancer and psychiatric care professionals to address the gap in cancer care for people with mental disorders.